Mapping of the UGT1A locus identifies an uncommon coding variant that affects mRNA expression and protects from bladder cancer - Tang, Wei (Oxford University Press, 2012)
A recent genome-wide association study of bladder cancer identified the UGT1A gene cluster on chromosome 2q37.1 as a novel susceptibility locus. The UGT1A cluster encodes a family of UDP-glucuronosyltransferases (UGTs), which facilitate cellular detoxification and removal of aromatic amines. Bioactivated forms of aromatic amines found in tobacco smoke and industrial chemicals are the main risk factors for bladder cancer. The association within the UGT1A locus was detected by a single nucleotide polymorphism (SNP) rs11892031. Now, we performed detailed resequencing, imputation and genotyping in this region. We clarified the original genetic association detected by rs11892031 and identified an uncommon SNP rs17863783 that explained and strengthened the association in this region (allele frequency 0.014 in 4035 cases and 0.025 in 5284 controls, OR = 0.55, 95%CI = 0.44–0.69, P = 3.3 × 10(−7)). Rs17863783 is a synonymous coding variant Val209Val within the functional UGT1A6.1 splicing form, strongly expressed in the liver, kidney and bladder. We found the protective T allele of rs17863783 to be associated with increased mRNA expression of UGT1A6.1 in in-vitro exontrap assays and in human liver tissue samples. We suggest that rs17863783 may protect from bladder cancer by increasing the removal of carcinogens from bladder epithelium by the UGT1A6.1 protein. Our study shows an example of genetic and functional role of an uncommon protective genetic variant in a complex human disease, such as bladder cancer.